Impact of ovalbumin allergy on oral and gut microbiome dynamics in 6-week-old BALB/c mice - Qiao, Chuanyue; Bian, Shuang; Huang, Hao; Xiao, Han; Ma, Lei; Han, Rui (Frontiers in Microbiology, 2024)
The gut microbiota is known to have a significant impact on the development of food allergyies, and several recent studies have suggested that both oral microbiota, which first come into contact with allergenic foods, may have a profound influence on the development of food allergyies.In this study, we have established an ovalbumin-sensitive mice model by utilizing ovalbumin as a sensitizing agent. Subsequently, we performed a comprehensive analysis of the gut and oral microbiota in ovalbumin-sensitive mice and the control mice using full-length 16S rRNA sequencing analysis.Results: Interestingly, both the gut and oral microbiota of ovalbumin-sensitized mice exhibited significant dysbiosis. The relative abundance of s__Lactobacillus_intestinalis in the gut microbiota of ovalbumin-sensitive mice exhibited a significant decrease, whereas the abundance of s__Agrobacterium_radiobacter and s__Acinetobacter_sp__CIP_56_2 displayed a significant increase. Furthermore, the relative abundance of s__unclassified_g__Staphylococcus, s__Streptococcus_hyointestinalis, and s__unclassified_g__Dechloromonas in the oral microbiota of ovalbumin-sensitive mice revealed a significant decrease. In contrast, the abundance of 63 other species, including s__Proteiniclasticum_ruminis, s__Guggenheimella_bovis, and s__Romboutsia_timonensis, demonstrated a significant increase. The random forest classifier achieved the best accuracy in predicting the outcome of food allergyies using three gut and three oral biomarkers, with accuracies of 94.12% and 100%, respectively. Based on the predictions of the PICRUSt2 analysis, the only consistent finding observed across multiple samples from both the groups of mice was a significant up-regulation of the nucleotide-binding oligomerization domain (NOD)-like receptor signaling pathway in the ovalbumin-sensitized mice.